KEDUDUKAN SUAMI DALAM SISTEM KEKERABATAN MASYARAKAT ADAT DITINJAU DARI PERSPEKTIF HAK ASASI MANUSIA (STUDI PADA DESA LETWURUNG KECAMATAN BABAR TIMUR KABUPATEN MALUKU BARAT DAYA) - Mahrita A. Lakburlawal (Faculty of Law, Universitas Pattimura, 2014)
Human rights emphasizes that humans are free to choose their actions, have the same potition regardless of race, religion, skin color or gender and is a manifestation of human dignity as stipulated in the constitution of 1945 and Law No.39/1999 on Human Rights. In the Letwurung village, based on kinship systems adopted by indigenous communities, put men who are married have a weak position in the family of his wife. The main issue is the kinship system is adopted by villagers Letwurung and how position of men who have married in the indegeneous kinship system. The Letwurung village has matrilineal kinship system so that married men in this community haves a weak position in the customary family law and child is entitled to the inheritance. It is discrimination against civil rights of men as a father and a leader of his family.